Development of Information Systems in the Jayapura Regency Regional Disaster Management Agency - Rimindubby, Vriska D.S; Satyarno, Iman; Saputra, Ashar (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2023)
BPBD Jayapura Regency is a government agency that coordinates and handles disaster issues in the Jayapura Regency. Jayapura Regency has geographical, geological, hydrological, and demographic conditions that have the potential for disasters that need to be handled both pre-disaster, during emergency response, and post-disaster. Disaster information delivery, both knowledge about disaster or disaster reports to the community, information on BPBD activities, and news about BPBD is currently carried out through socialization in the community. So that there are often many conflicts due to incorrect news in the community related to BPBD's work programs, besides that BPBD Jayapura Regency itself does not yet have an integrated communication media that is directly connected to the people of Jayapura Regency. System An Information system in the form of a website was built to help related parties, namely BPBD Jayapura Regency and the community to be directly connected. This system was built using XAMPP as a web server and MySQL as a database server using the SQL programming language, PHP programming language is run on the server side so that the website becomes more dynamic. The analysis method used Use Case Diagram as a description of interactions that occur in the system. This system provides disaster reporting and complaint services This system also helps the BPBD in displaying information related to BPBD and disasters. This system will display information to the community and access to view disaster data reports that occur in the village added by each village or district head in Jayapura Regency.